Prarancangan Pabrik Dimetil Eter Proses Dehidrasi Metanol Dengan Katalis Alumina Kapasitas 21.000 Ton Per Tahun - Gunawan, Indra; , Kusmiyati, S.T, M.T, Ph.D; , Tri Widayatno,S.T., MS.c., Ph.D (2015)
DME (dimethyl ether) is one of the compounds to be used as an alternative fuel. DME (dimethyl ether) has physical properties similar to liquefied petroleum gas that can be directly used as an energy source for household appliances. Industrial development opportunities DME (dimethyl ether) in Indonesia is quite large, because the energy needs in Indonesia continues to increase, it is necessary to plan the design of chemical plants with products DME (dimethyl ether). The factory is planned to operate for 330 days/year with a production capacity of DME (dimethyl ether) amounted to 21,000 tons/year. The main raw materials required are as much as 99.95% methanol 27253.74344 tons/year. The plant will be established in Bontang , East Kalimantan province where the mill site near the Mahakam river, so that the source of water for the unit comes from river water utilities. Production of DME (dimethyl ether) using methanol dehydration process with alumina catalyst ( Al2O3 ) at a pressure of 14.9 atm and a temperature of 250°C where the reactor is used multitube fixed bed reactor. The reaction is exothermic and operates on a non-isothermal non-adiabatic conditions. Where in the reactor using a coolant in the form of DOWTHERM A. Calculation of economic evaluation results of fixed capital needed is Rp 230,096,936,629.89 and working capital of Rp 77,903,484,166.90. Return On Investment acquired before tax (ROIb) amounted to 23.58% and return on investment after tax (ROIa) amounted to 16.50%. Pay Out Time before tax (POTb) by 2.98 years and Pay Out Time after tax (POTa ) was 3.8 years. With Break Even Point (BEP) of 52.77%, Shut Down Point (SDP) of 26.98% and a Discounted Cash Flow (DCF) of 36.69%. Based on consideration of the results of these evaluations, the DME plant with a capacity of 21,000 tons/year is feasible to set up.